Actigraphic assessment of periodic leg movements in patients with restless legs syndrome. (26th March 2013) - Cippà, Maria A. T.; Baumann, Christian R.; Siccoli, Massimiliano M.; Bassetti, Claudio L.; Poryazova, Rositsa; Werth, Esther
Summary: The diagnosis of restless legs syndrome (RLS) relies upon diagnostic criteria which are based on history only, and dopaminergic treatment is not normally the first choice of treatment for all patients. It would be worthwhile to identify patients non‐responsive to dopaminergic treatment beforehand, because they may suffer from a restless legs‐like syndrome and may require alternative treatment. We included retrospectively 24 adult patients fulfilling the four essential criteria for restless legs and 12 age‐matched healthy controls. They were investigated by ambulatory actigraphy from both legs over three nights, and patients started treatment with dopamine agonists after this diagnostic work‐up. We examined 12 responders to dopaminergic treatment and 12 non‐responders and studied the association between response to dopaminergic treatment and the periodic limb movement index (PLMI) as assessed with actigraphy. Demographic characteristics, excessive daytime sleepiness and fatigue at baseline were similar in all three groups. Baseline RLS severity was similar between responders and non‐responders [International Restless Legs Severity Scale (IRLS): 25 ± 9 and 24 ± 8]. Group comparisons of PLMI before treatment initiation showed significant differences between the three groups. Post‐ho c pairwise comparisons revealed that healthy controls had significantly lower PLMI (4.9 ± 4.5) than responders (29.3 ± 22.7) and non‐responders (13.3 ± 11.2). Similarly, the PLMI in responders was lower than in non‐responders. PLMI day‐to‐day variability did not differ between responders and non‐responders and there was no correlation between treatment effect, as assessed by the decrease of the IRLS and baseline PLMI. Our retrospective study indicates that actigraphy to assess periodic limb movements may contribute to a better diagnosis of dopamine‐responsive restless legs syndrome.